Analysis Implementation of Operational Funds School In Increase Teacher Personality - H. Soro , Suharyanto; Handayani, Neng Kiki; Rohimah, Dewi (Civiliza Publishing, Indonesia., 2025)
Study This discuss utilization strategic aid fund Operational School (BOS) in increase competence the personality of teachers at SDN 235 Lengkong Kecil, a school the basis of the country in Bandung which is facing challenge diversity background behind social and formation character students . Competence teacher personality which includes stability emotion , maturity , wisdom , and authority acknowledged as factor important in create environment positive learning​ as well as become example for students . Purpose study This is analyzing BOS funds allocated and implemented For support development teacher personality . With use approach studies case , data collected through observation participatory , interview deep with leader school and teachers, analysis document report finance school (RKAS), as well as towards development programs personality . Research results show that the BOS funds at SDN 235 Lengkong Kecil are partly big used For need operational and administrative , some funds are allocated For activity teacher development such as internal training on integrity and ethics profession , reflection forum ethical regularly , and activity formation characters that involve figure community . Initiatives This proven increase discipline , motivation , and solidarity between teachers, so that create climate more school​ harmonious and better teacher - student relationship good . However , research also found challenge like activities that are of a nature incidental and not yet listed in planning , as well as difference priority between stakeholders interests that sometimes hinder optimization utilization of funds. Conclusion from study that school the Already do utilization of boss funds in accordance with luck , but Still there is lack so that No cover all school programs.